Agency of Dalit Subaltern and Resistance in Rabindra Nath Tagore’s Chandalika - Binadi, Chet Raj (Contemporary Research: An Interdisciplinary Academic Journal, 2023)
The purpose of this article is to analyze the agency of Dalit subaltern people and their resistance in Rabindranath Tagore’s Chandalika. The play has been mostly interpreted either as a play of religious conflict or a psychological drama. Such readings have however obliterated the most social concerns of the play like casteism and the agency of the Dalit people which make the play more as a social manifesto than merely stage performance and realm of aesthetics. This study looks at the issue of marginalized Dalit subaltern people focusing on how the true agency is denied to them and made hegemonic. The denial of agency to the subaltern people weakens their spirit of resistance and compels them to accept domination hegemonically. Maya, the mother character in the drama is hegemonized character in the play and gives consent to the caste system to function intimidatingly upon them. On the other hand, the performative gestures that are used consistently by Prakiti is an act of resisting the petrified and, static norms of the society. Thus, this paper focuses to explore the agency of subaltern people and throws light on the conception of resistance using the theoretical insights of Antonio Gramsci, Spivak and Michael Garnet.